2019
DOI: 10.1002/cphc.201900858
|View full text |Cite
|
Sign up to set email alerts
|

Water Diffusion and Transport in Oil Paints as Studied by Unilateral NMR and 1H High‐Resolution MAS‐NMR Spectroscopy

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…Finally, in PbLO 5:1, two types of water, one free (T 2w ) and one bound (Tʺ 2w ), were observed. These results are similar to those reported in our previous study 27 . Also, in this case, the appearance of a second domain of water may be due to the formation of hydrated ionic group clusters.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, in PbLO 5:1, two types of water, one free (T 2w ) and one bound (Tʺ 2w ), were observed. These results are similar to those reported in our previous study 27 . Also, in this case, the appearance of a second domain of water may be due to the formation of hydrated ionic group clusters.…”
Section: Resultssupporting
confidence: 93%
“…Unilateral NMR permits the open porosity available to the diffusion of water and solvents in different materials to be determined 27 , 28 . In this article, with ‘open porosity’ we refer to the void fraction or ‘empty’ spaces that may be filled by water or organic solvents in contact with the paint film.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the shortest component, T 2A , of about 0.1 ms, involves a majority of the protons (85% of the population); an intermediate component, T 2B , of about 0.5 ms, involves~10% of the protons; and the longest component, T 2C , of about 1 ms, involves 3% of the protons. Interestingly, these results are remarkably similar to those found in the model oil paintings studied and reported in [35]. In our samples, a slight shortening of the T 2 values was observed with respect to the model oil paints.…”
Section: Unilateral Nmr To Evaluate Water-based Cleaning Systems Applsupporting
confidence: 92%
“…HR-MAS has been used to study the degradation of cellulose in the paper due to water [33,34]. More recently, we have used HR-MAS in combination with unilateral NMR to analyze the diffusion of water in lead oil paintings [35]. In this study, HR-MAS NMR spectroscopy was exploited to study linseed oil, shellac, colophony and sandarac to chemically distinguish these compounds in paintings using a reduced amount of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Soap formation is another cause of painting degradation. Tullio et al [17] studied the effect that moisture content has on linseed oil-based painting water absorption. They found that the thicker paintings and those subjected to the highest relative humidity (irrespective of the time period) showed a higher degree of absorption.…”
Section: Paint Layer Insightsmentioning
confidence: 99%